2011
DOI: 10.1074/jbc.m111.242354
|View full text |Cite
|
Sign up to set email alerts
|

FtsH-dependent Processing of RNase Colicins D and E3 Means That Only the Cytotoxic Domains Are Imported into the Cytoplasm

Abstract: It has long been suggested that the import of nuclease colicins requires protein processing; however it had never been formally demonstrated. Here we show that two RNase colicins, E3 and D, which appropriate two different translocation machineries to cross the outer membrane (BtuB/Tol and FepA/TonB, respectively), undergo a processing step inside the cell that is essential to their killing action. We have detected the presence of the C-terminal catalytic domains of these colicins in the cytoplasm of target bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 69 publications
5
58
0
Order By: Relevance
“…We have shown that only the cytotoxic C-terminal, catalytic domains are detected in the cytoplasm of cells exposed to DNase colicins, as in the case of RNase colicins [10]. The same 18.5 kDa processed form was detected in OmpT-deficient cells treated with colicins E2 or E7 (Figure 1).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We have shown that only the cytotoxic C-terminal, catalytic domains are detected in the cytoplasm of cells exposed to DNase colicins, as in the case of RNase colicins [10]. The same 18.5 kDa processed form was detected in OmpT-deficient cells treated with colicins E2 or E7 (Figure 1).…”
Section: Discussionmentioning
confidence: 68%
“…As a consequence, only the cytotoxic C-terminal domains were detected in the cytoplasm of colicin D or E3-exposed cells [10], [11]. During the last few years, the essential, inner-membrane signal-peptidase LepB was shown to be required specifically for the toxicity of colicin D, whereas the inner-membrane protease FtsH is required for the toxicity of all nuclease colicins [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Two models have been proposed for the role of FtsH in colicin import. De Zamaroczy and coworkers have shown that FtsH is required for the release of colicin nucleases into the cell, and they hypothesize that the protease directly cleaves the domain (23,32). Kleanthous and coworkers have proposed that the ATP-dependent unfoldase activity of FtsH is used to pull the nuclease domain into the cell (24).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, toxin activation provides an additional opportunity for target cells to evolve resistance to CDI UPEC536 because cysK is not an essential gene. In contrast, soluble bacteriocins also deliver toxic domains into bacteria to inhibit growth, but typically only require cell envelope proteins for recognition and translocation of the toxin (Cascales et al 2007;Chauleau et al 2011). One exception appears to be colicin M (an inhibitor of peptidoglycan synthesis), which is remodeled into its active conformation by a peptidylprolyl cis-trans isomerase (FkpA) in the periplasm of target cells (Schaller et al 1982;El Ghachi et al 2006;Hullmann et al 2008;Helbig et al 2011).…”
Section: Discussionmentioning
confidence: 99%